Gendered Agency in (post-) conflict spaces - Henrizi, Annika (My University, 2017)
What role do women play in civil society in post-conflict Iraq, what kind of challenges do arise and how do they regard their own engagement relating to Iraqi society? Until now, research on Iraq post 2003 has focussed on the aftermath of war, processes of political institution building and democratization. International peacebuilding efforts in Iraq have been widely criticised by practitioners and academics. Without neglecting these critiques, I elaborate how external intervention has also created spaces for Iraqi women to exercise different forms of agency. Critical approaches in peace and conflict studies often limit so-called “local” agency to resisting liberal agendas, assuming persistent binaries between local and international spaces. I seek to outline a concept of gendered agency that integrates a relational conceptualisation of space into the hitherto applied understandings of agency. Drawing on empirical evidence from Iraq, I elaborate how a relational theory of space contributes to grasping hybrid realities and notions of agency on the ground. Beyond analysing spaces of agency for women in (post-) conflict Iraq, I discuss the value of incorporating a relational understanding of space into critical peacebuilding studies.
The Engagement of Iraqi Women in NGOs
Keywords: Konflikt; Feminismus; Gesellschaft; Politik; Aktivismus; Agency; Raum; Gender; 303 Gesellschaftliche Prozesse; Frieden; Irak